Water, an Agent of Purification and Life Sustenance: The Relationships of Women with Water in the Southern Provinces of Nigeria - Ekpenyong Mfon, Etim (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In traditional Nigerian societies, women and girls predominantly bear the responsibility of fetching water, reflecting their nurturing roles within families and communities. Water is essential for domestic tasks like cooking, laundry, and child bathing, positioning women as the primary gatherers. Many Nigerian cultures link water with healing, purification, fertility, and life, often involving women in rituals that promote well-being and restore balance. This paper explores multi-ethnic Nigerian beliefs about women and water, with a special focus on the Igbo people. Over six months, interviews with women from various ages and social statuses provided diverse perspectives on these cultural practices. Key findings reveal the significant roles women play in festivals such as the Osun Festival in Osogbo, the Igue Festival in Benin City, and the Yemoja Festival in Ibadan, where rituals are centered around rivers and women are pivotal participants. Additionally, in many Nigerian cultures, it is frowned upon for men to perform domestic chores or fetch water, as these tasks are traditionally assigned to women. The study underscores the central role of women in water-related activities and rituals, emphasizing the need for policies that address the unique challenges women face in accessing water and sanitation.